Post a New Question

Trigonometry Check

posted by .

Simplify #3:
[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx]
= [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx]
= [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx]
= [cosx-cosxsinx]/[cosx+cosxtanx]
= [cosx(1-sinx]/[cosx(1+tanx]
= (1-sinx)/(1+tanx)

Is this correct???

  • Trigonometry Check -

    looks good to me

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question